From access to engagement and beyond - Billingham, Stuart (Emerald Publishing Limited, 2022)
This collection reveals a recurring theme in the author's work over almost three decades: that the preoccupation in policy, commentary, research and practice with who gets into higher education has led to a corresponding failure to cast a critical eye over what, where and when they get the higher education offer. It seems that potential students are expected to fit-in with HE culture, rather than think about how HE might change to fit-in with them. On offer is a collection of the author's works, spanning much of his professional working life, covering issues relevant to widening access to success in higher education and for a wide-ranging audience. Some chapters offer conference speeches and keynotes; others are blogs or chapters in books. One is even a speech to an audience from the UK House of Lords delivered originally within the Parliament precincts. Together they paint a picture of the prevailing issues and concerns of the widening access agenda over twenty-five years. A recurring call throughout is the need for greater international collaboration, a need that has indeed grown in importance as the conversation on widening access and success has progressed. Some would say that this is due, in no small measure, to the work of this critical thinker and practitioner.
Keywords: Higher education.; Educational equalization.; Education -- Higher.; Higher & further education, tertiary education.; elektronické knihy; electronic books